2016
DOI: 10.1158/1078-0432.ccr-16-0155
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Stratification and Differential Risk by Breast Cancer Index and Recurrence Score in Women with Hormone Receptor–Positive Lymph Node–Negative Early-Stage Breast Cancer

Abstract: Purpose: Previous results from the TransATAC study demonstrated that both the Breast Cancer Index (BCI) and the OncotypeDX Recurrence Score (RS) added significant prognostic information to clinicopathologic factors over a 10-year period. Here, we examined cross-stratification between BCI and RS to directly compare their prognostic accuracy at the individual patient level.Experimental Design: A total of 665 patients with hormone receptor-positive (HR þ ) and lymph node-negative disease were included in this ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 20 publications
0
18
0
1
Order By: Relevance
“…RS results were compared to BCI in one study, with MMP in four studies, with ROR in four studies, and with EP/EPclin in one study . One further study, the 2016 TransATAC study, compared RS with BCI, ROR and EPclin . As to nodal status, three of 14 studies included node‐negative patients only (RS vs .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…RS results were compared to BCI in one study, with MMP in four studies, with ROR in four studies, and with EP/EPclin in one study . One further study, the 2016 TransATAC study, compared RS with BCI, ROR and EPclin . As to nodal status, three of 14 studies included node‐negative patients only (RS vs .…”
Section: Resultsmentioning
confidence: 99%
“…MMP by Maroun et al . 2015), while 11 of 14 studies included node‐positive patients as well . A list of the studies is shown in Table .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this issue of Clinical Cancer Research, Sestak and colleagues (1) compare the performance of a 7 gene prognostic score (Breast Cancer Index, BCI, Biotheranostics, San Diego, CA), with a 21 gene prognostic score (Oncotype Dx, RS, Genomic Health, Redwood City, CA) in a retrospective cohort of 665 patients with hormone receptor positive, lymph node negative early stage breast cancer treated with tamoxifen or anastrozole alone (no chemotherapy) in the Anastrozole, Tamoxifen, Alone or in Combination (ATAC) trial. In particular, these authors compare the prognostic accuracy of both in cases where these assays yielded discordant results.…”
mentioning
confidence: 99%